FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT KARIR MAHASISWA AKUNTANSI (Studi Empiris Mahasiswa Akuntansi di Universitas di Kota Semarang) - Prima Trihutama; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
This research aim to identify analyze  faktors that influence of interest accounting students career selection research referse to widiatami ( 2013 ). Faktors influencing the selection of career are measured by variable financial rewards, profesional training, social values, profesional recognation,work environment, level of student, and gender as kontrol variabel.The research data is found by stratified sampling technics for undergraduate accounting students in UNDIP, UNNES, UNISSULA, UNIKA USM, UDINUS, dan UNISBANK There are 97 total samples of students from total 3295 students by using Slovin formula.  Data analysis in this research uses Multinomial regresi Logistic method with SPSS 19.00 for Windows.The result of the research shows that faktors : financial rewards, professional recognation, work environment, and level of student influence the choice of carrier of accounting students.  While social values and profesional training does not influence the choice of carrier of accounting students.